Avaliação do efeito cardioprotetor do extrato aquoso das folhas de Rudgea virbunoides benth. em ratos com hipertensão renovascular - Fernanda Viana Paulin (2021)
Systemic arterial hypertension (SAH) is a multifactorial clinical condition characterized by elevated and sustained blood pressure levels. It is also the main risk factor for functional and / or structural changes in target organs and metabolic changes, with a consequent increase in the risk of fatal and non-fatal cardiovascular events. Treatment for the control of SAH includes actions to change lifestyle and use medications, such as diuretics, sympatholytics, vasodilators, calcium channel blockers, angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers. In this context, treatment with the administration of herbal medicines or the use of medicinal plants in forms of teas, infusion and macerations is also inserted. It is known that some chemicals present in certain plants are associated with the prevention or treatment of cardiovascular diseases (CVD), for example.Rudgea viburnoides Benth. it belongs to the Rubiaceae family, popularly known as congonha, congonha-de-bugre or bugre and used in traditional medicine in the form of tea, due to its anti-rheumatic, diuretic, hypotensive and blood purifying properties. It is a common species of the Cerrado and has a diuretic and antioxidant potential already described. The aim of this study was to evaluate the effects of prolonged administration of aqueous extract obtained from Rudgea Viburnoides (Cham.) Benth. (AERV) leaves on the impairment of oxidative stress, renal dysfunction and cardiovascular damage in hypertensive 2K1C rats. In addition, also determine the chemical composition of AERV through high performance liquid chromatography coupled to the diode array detector and mass spectrometry (CLAE-DAD-EM). For this, the AERV was obtained through accelerated solvent extraction and this extract was analyzed by HPLC-DAD-EM. In addition, an acute toxicity test was also performed on female Wistar rats. Renovascular hypertension (two kidneys, model of a clip) was surgically induced in male Wistar rats. AERV was administered orally in doses of 30, 100 and 300 mg / kg, for 28 days, daily for 5 weeks after the surgery. On days 1, 7, 14, 21 and 28, renal function was assessed by diuresis, as well as urinary electrolytes, pH and density. On the 29th day, blood pressure and heart rate were recorded by electrocardiography. Blood samples were also obtained to evaluate the activity of the plasma angiotensin-converting enzyme and to measure serum Na+, K+, urea and creatinine. Subsequently, the cardiac and mesenteric vascular beds were isolated, respectively, for cardiac morphometry and assessment of vascular reactivity. At the end, samples of the aorta, heart and kidney were collected for evaluation of tissue oxidative stress. Through the analysis by HPLC-DAD-EM, the compounds identified in the AERV were quinic acid, as well as chlorogenic acids, a glycosylated iridoid, O- glycosylated flavonols, saponins and a triterpenes. In the assessment of acute toxicity, no sign was observed after treatment with a single dose of AERV. Prolonged treatment with AERV in hypertensive rats was able to preserve urinary excretion and electrolyte levels (Na+, K+, Ca2+ and Cl-) in a similar way to the group operated by Sham (negative control). In addition, prolonged treatment with AERV was able to reverse electrocardiographic changes, increase in blood pressure and heart rate in 2K1C hypertensive rats, as well as reverse left ventricular hypertrophy and changes in vascular reactivity induced by hypertension. Thus, this effect was associated with positive modulation of tissue oxidative stress, activation of the NO / cGMP pathway and inhibition of the angiotensin converting enzyme, which indicates a potential mechanism for the renal and cardiovascular effects of AERV. Thus, it can be said that the 28-day treatment with AERV reduced the progression of cardiorenal disease in 2K1C hypertensive rats.